Sistem Informasi Pengawasan Aset di Dinas Pendidikan Kota Surakarta untuk Meningkatkan Efisiensi dan Transparansi - Dwi Arif Nur Utomo; Agus Rianto; Jani Kusanti (Universitas Darul Ulum, 2024)
Asset monitoring at the Surakarta City Department of Education is still carried out manually by visiting all related institutions that receive financial aid. This activity is conducted daily every year and consumes a significant amount of labor, time, and costs, potentially leading to inefficiencies, data recording errors, and a lack of transparency in the asset reporting and monitoring processes. These issues can hinder decision-making processes related to asset management and reduce the accountability of relevant parties. This research aims to develop a web-based Asset Monitoring Information System using PHP and MySQL to enhance efficiency and transparency in asset management. The system development method used is the System Development Life Cycle (SDLC), which includes the stages of planning, needs analysis, design, implementation, and system testing. The results of this research show that the developed system can accelerate the asset management process, minimize data errors, and improve the accessibility and transparency of asset reporting. The system also facilitates real-time asset monitoring and simplifies the validation process by authorized personnel. The designed system is expected to improve operational efficiency and accountability in asset monitoring at the Surakarta City Department of Education.